Transformasi Pembelajaran Pancasila: Penerapan Student-Centered Learning di Kalangan Mahasiswa Pendidikan Agama Islam - Trisno, Bambang; Hidaytullah, Syarif (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to analyze the differences in Pancasila learning outcomes between students who use the Student-Centered Learning (SCL) method and the conventional method. The research method uses an experimental approach with a control group design. The subjects of the study consisted of 60 PAI students who were divided into two groups: the SCL group and the conventional group, each consisting of 30 students. The results showed that the SCL group had a higher average score, which was 85.4 with an understanding level of 92%, compared to the conventional group which had an average score of 75.2 and an understanding level of 78%. These findings indicate that SCL is effective in improving Pancasila learning outcomes. However, this study has limitations in scope which only covers one study program at one university. Therefore, further research is needed to test the effectiveness of SCL in a broader context. In addition, educators are advised to integrate SCL in Pancasila learning in order to improve student learning outcomes as a whole.